The Economy Begins in the Family - Michalski, Michal A. (Demographic Challenges in Central Europe: Legal and Family Policy Response, 2024)
This chapter presents the fundamental role of the family as the basic and primary social group for the existence and prosperity of the economy. Economic activity in modern societies is largely organised and conducted by formalised economic organisations. However, within their households, families produce goods and services that constitute an important part of GDP. Families also consume – as well as ‘prosume’ – distribute, and exchange wealth, and accumulate capital. In addition to examining the role of the family as the basic economic unit, this chapter describes and explains how the functioning of the family creates the necessary ground for the economy and conditions its multidimensional continuity, socio-economic reproduction, and development. In this context, various roles of the family are presented and explained, from the procreative function, which generates population replacement, through the socialisation, education and economic functions. The family is, thus, justifiably presented as an irreplaceable factory of human and social capital and a transmission belt of culture. The chapter collects and combines contributions and arguments from various disciplines, including economics, anthropology, cultural studies, and sociology.Keywords: economy, family, socio-economic reproduction, development, human capital, social capital.